The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11606-018-4655-8
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Interventions Designed for Women: an Evidence Map

Abstract: BACKGROUND: Telehealth employs technology to connect patients to the right healthcare resources at the right time. Women are high utilizers of healthcare with genderspecific health issues that may benefit from the convenience and personalization of telehealth. Thus, we produced an evidence map describing the quantity, distribution, and characteristics of evidence assessing the effectiveness of telehealth services designed for women. METHODS: We searched MEDLINE ® (via PubMed ® ) and Embase ® from inception thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 78 publications
(49 reference statements)
0
26
0
Order By: Relevance
“…Internet-based interventions make it possible to tailor healthcare considering gender-specific healthcare needs. According to a recent review, there is a need to examine the effects, efficiency and acceptability of telehealth for women to inform efforts to implement it (Goldstein et al., 2018). In our review, we focused on the effects of internet-based interventions for women with chronic pain in order to analyse the options, results and methodological quality of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet-based interventions make it possible to tailor healthcare considering gender-specific healthcare needs. According to a recent review, there is a need to examine the effects, efficiency and acceptability of telehealth for women to inform efforts to implement it (Goldstein et al., 2018). In our review, we focused on the effects of internet-based interventions for women with chronic pain in order to analyse the options, results and methodological quality of research.…”
Section: Discussionmentioning
confidence: 99%
“…Women are high utilisers of healthcare. Considering biological and sociocultural characteristics, including specific work and family-related demands, they have gender-specific healthcare needs that may benefit from specific internet-based interventions (Goldstein et al., 2018). In this regard, performing a gender analysis is relevant to determine the effectiveness of internet-based interventions, which may lead women to adopt a more proactive behaviour in the treatment, maintenance and follow-up of their pain.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…87 VA recently commissioned and published an evidence map on telehealth services designed for women, with a section dedicated to using telehealth for high-risk breast cancer assessment. 88 However, the authors note that none of the studies in this section were conducted in VA. The authors further note that there is a dearth of studies examining use of telehealth in women aged 60 years and older or the intersection between telehealth use and patient race and ethnicity.…”
Section: Palliative and Supportive Carementioning
confidence: 98%
“…There is limited data on the safety and efficacy of telemental health treatment for individuals who actively experience intimate partner violence (IPV) [ 44 ]. A systematic review of studies on using V-TMH for people who have experienced IPV only found a small number of studies, and most of these studies focused on women [ 44 ]. Other such studies on telehealth were designed for women in domestic violence shelters or mental health clinics [ 45 , 46 ].…”
Section: Ethical Considerations In V-tmhmentioning
confidence: 99%